Efektivitas Penegakan Hukum terhadap Kekerasan Anak di PAUD: Tinjauan Yuridis dan Upaya Pemulihan Korban - Soviana Nadia Nadia; Eny Nur Aisyah (Institut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2025)
Violence against children in Early Childhood Education (PAUD) settings remains a serious issue despite explicit regulations in the Child Protection Law and the National Education System Law. This study aims to analyze the legal norms related to child protection, assess the effectiveness of their implementation in PAUD institutions, and formulate recommendations to strengthen child protection efforts. Using a normative juridical research method through literature review of legislation, scholarly journals, and case reports, the study finds that although regulations on child protection and sanctions for perpetrators are comprehensive, their implementation remains weak due to the absence of anti-violence SOPs, limited teacher competence, and inadequate reporting mechanisms in PAUD settings. The study recommends the development of child protection guidelines in every PAUD institution, capacity-building for teachers through violence-prevention training, and the strengthening of recovery services and psychological support for child victims as essential efforts to create a safe educational environment.